Pengenalan Media Digital Pada Usaha Mikro Kecil dan Menengah (UMKM) Melalui Diskusi dan Sharing di Desa Bukit Tinggi Kecamatan Gunungsari - Arbain arbain; Arman Koko; Artam Hadi; Baiq Nurcahya; Dodi Al Fayet; Fathullah Akbar; Lalu Rizky DS; M.Sopian Hadi; Pasrah Setiawati; Rizky Gagah W; Salsabilla Aurelia EP; Baiq Azizah Haryantini (Universitas Mataram, 2021)
This activity aims to introduce digital media to Micro, Small and Medium Enterprises (MSMEs) actors, in Desa Bukit Tinggi. The introduction was carried out with the method of discussion and sharing about digital media to promote the results of MSMEs. The targets of this discussion and sharing are teenagers, MSME actors and Bukit Tinggi Village administrators. Resource persons, namely students of the Communication Science study program and digital media experts from HSG Media. During this discussion and sharing, participants were introduced to digital and technical media in making materials to complement digital media, participants be able to create good and correct and interesting content starting from the process of creation, editing to the process of being posted on social media. For sustainability, participants are expected to be practitioners or initiators in managing digital media as a forum for MSME activists to market products or crafts produced by the local community. Participants' interest and enthusiasm for the material provided was quite high, as seen from the many questions from participants and discussions with resource persons to deepen and strengthen knowledge in digital media.